2003
DOI: 10.1159/000070090
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Treatment regarding Articulation, Resonance and Voice in Flemish Adults with Unilateral and Bilateral Cleft Palate

Abstract: The purpose of this study was to evaluate the outcome regarding speech intelligibility, articulation, nasalance, nasality and voice in adult cleft palate patients. An additional objective of this study was to delineate the impact of a unilateral versus bilateral cleft lip and palate on speech outcome and to compare the nasalance and nasality patterns of cleft palate adults with data from non-cleft subjects. Objective (nasalance values obtained by the Nasometer, mirror-fogging test according to Glatzel and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
6
11
1
5
Order By: Relevance
“…The voice quality measured with DSI was normal or just slightly reduced in the CLP children. Our results are in accordance with van Lierde et al's results [34,52,53].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The voice quality measured with DSI was normal or just slightly reduced in the CLP children. Our results are in accordance with van Lierde et al's results [34,52,53].…”
Section: Discussionsupporting
confidence: 94%
“…In contradiction to Karling et al [38], no significant differences between UCLP and BCLP were reported in this study which might be related to the number of tested subjects. In 2003, however, van Lierde et al [52] confirmed their earlier results of 2002 [34] with fewer subjects. According to Hardin-Jones and Jones [61], fewer children with isolated cleft palate of the soft palate show hypernasality than children with combined cleft lip and palate.…”
Section: Discussionmentioning
confidence: 75%
“…But no other reports were found who investigated the speech characteristics after BSSO in Flemish speaking adults. From this study and from previous studies in cleft palate patients 24 it seems that in the Flemish language the /r/ is a vulnarable sound for distortions. The / r/ in the Flemish language has a different place of articulation then the /r/ in the English language.…”
Section: Discussionsupporting
confidence: 70%
“…Their nature cannot be explained by this study. Probably the /r/ and the /s/ are vulnerable sounds for dis- [25,26] . Remarkably enough only 1 subject showed 1 year after surgery a compensatory articulation disorder (CAD), specifically a palatal stop.…”
Section: Discussionmentioning
confidence: 99%